2015
DOI: 10.5897/err2015.2194
|View full text |Cite
|
Sign up to set email alerts
|

Developing competency of teachers in basic education schools

Abstract: This study aims to develop competency of teachers in basic education schools. The research instruments included the semi-structured in-depth interview form, questionnaire, program developing competency, and evaluation competency form. The statistics used for data analysis were percentage, mean, and standard deviation. The research found that factors of competency were: 1) the persistence in learning management and work practice, 2) competency in planning, goal setting, learning management and work practice, 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…This result asserted thoughts proposed by [3] which ensured that "deep design" was a term used by purposefully to distinguish student-and learning-centred lesson planning from the classroom-centred activity-oriented planning that is common among beginning teachers. These results were also supported by [8] who found that factors of competency were: 1) the persistence in learning management and work practice, The study also used a satisfaction instrument developed by the AGU quality and excellence center administrated at the end of the course. Analysis of data revealed a high level of satisfaction with the course material i.e.…”
Section: Discussion Of Results and Conclusionsupporting
confidence: 59%
See 1 more Smart Citation
“…This result asserted thoughts proposed by [3] which ensured that "deep design" was a term used by purposefully to distinguish student-and learning-centred lesson planning from the classroom-centred activity-oriented planning that is common among beginning teachers. These results were also supported by [8] who found that factors of competency were: 1) the persistence in learning management and work practice, The study also used a satisfaction instrument developed by the AGU quality and excellence center administrated at the end of the course. Analysis of data revealed a high level of satisfaction with the course material i.e.…”
Section: Discussion Of Results and Conclusionsupporting
confidence: 59%
“…In their study [8] The original set of instructional design competencies was developed in 1986 as a result of more than a year of research, discussion, and validation by a group of instructional design professionals and academicians [9]. The level of proficiency described in the 1986 competencies was taken to represent an instructional de- In response to this changing environment, the IBSTPI set out to review and revise the ID competencies in the year 2000 and, more recently, in 2012.…”
Section: Introductionmentioning
confidence: 95%
“…Since 2006, the key competences had become the most significant curricular element in compulsory education (Yuayai, Chansirisira, & Numnaphol., 2015;Méndez-Alonso, Méndez-Giménez, & Fernández-Río, 2015). However, the way they should be implemented in schools is not clear, since there are no protocols defined by law.…”
Section: Introductionmentioning
confidence: 99%